2012
DOI: 10.1155/2012/461873
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Carcinoma of the Ovary of Hypercalcemic Type: A Case Report

Abstract: Introduction. The small cell carcinoma of hypercalcemic type of ovary is a very aggressive tumor. It is associated with two-thirds of cases with hypercalcemia most often asymptomatic. It occurs mostly for young women. The treatment combines surgery, chemotherapy, and radiotherapy. Case Presentation. We report a case of small cell carcinoma of the ovary hypercalcemic type in a young Tunisian woman aged 25 years after a severe abdominal pain syndrome and a large ovarian mass discovered in scanner; a laparotomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, tumor stage is the most important prognostic factor. The overall survival rate is about 10% and reaches 30% when the tumor is stage IA (16). The overall prognosis of this tumor is poor (2,8).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, tumor stage is the most important prognostic factor. The overall survival rate is about 10% and reaches 30% when the tumor is stage IA (16). The overall prognosis of this tumor is poor (2,8).…”
Section: Discussionmentioning
confidence: 97%
“…But, it is desirable to preserve the fertility in young patients. Therefore, the conservative surgical treatment sparing the ovary and uterus is recommended in the early stages (16).For the higher stages or recurrent tumors, chemotherapy, radiotherapy, or both may improve survival (5).According to the study conducted by Young et al, favorable prognostic factors of small cell carcinoma include the localized stage of tumor, tumor size less than 10 cm, patient age above 30 years, and absence of large cells (2). However, tumor stage is the most important prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Related literature reported variable serum calcium levels of 2.43–4.80 mmol/L, with an average of 3.68 mmol/L. 2 , 4 , 6 11 In the present case, this patient had a much higher level of serum calcium of 4.90 mmol/L preoperative than what other literature reported, while postoperative serum calcium levels decreased to 1.9 mmol/L. Hence, on day 8, calcium levels had to be brought back up to the normal level, and it then stayed normal during the followups, which indicated that increased serum calcium levels were caused by tumor cells.…”
Section: Discussionmentioning
confidence: 99%